Oil price and exchange rates: a wavelet analysis for organisation of oil exporting countries members - Alatrturi, Basheer H. M.; Alshammri, Ahmad Alrazni; Tuan Hussin, Tuan Muhd Taufik; Saiti, Buerhan (www.econjournals.com, 2016)
This paper studies the relationship between oil price and the exchange rates of OPEC members from February 1999 to March 2016. The wavelet method is applied to combine information from both time and frequency domains, which does not require stationary and decomposition of original time series data. The study found that the strength of the relationship between oil price and exchange rate divides into three main categories, namely oil price leads exchange rate, exchange rate leads oil prices, and the relationship keeps changing. Countries which currencies pegged to USD are lagging against oil price changes, countries with floating exchange rates and countries with an undisclosed weighted basket of international currencies leads the changes in oil price, and countries which their currencies pegged to Special Drawing Right (SDR) experience changing relationships. This finding suggests that the central banks of OPEC member countries should give importance to shocks on oil prices, while formulating their own exchange rate policy.